Alzheimer's disease-related peptide PS2V plays ancient, conserved roles in suppression of the unfolded protein response under hypoxia and stimulation of ?-secretase activity - Nik, S.; Newman, M.; Wilson, L.; Ebrahimie, E.; Wells, S.; Musgrave, I.; Verdile, Giuseppe; Martins, R.; Lardelli, M. (Oxford University Press, 2015)
The PRESENILIN1 and PRESENILIN2 genes encode structurally related proteases essential for ?-secretase activity. Of nearly 200 PRESENILIN mutations causing early onset, familial Alzheimer's disease (FAD) only the K115Efx10 mutation of PSEN2 causes truncation of the open reading frame. If translated, the truncated product would resemble a naturally occurring isoform of PSEN2 named PS2V that is induced by hypoxia and found at elevated levels in late onset Alzheimer's disease (AD) brains. The function of PS2V is largely unexplored. We show that zebrafish possess a PS2V-like isoform, PS1IV, produced from the fish's PSEN1 rather than PSEN2 orthologous gene. The molecular mechanism controlling formation of PS2V/PS1IV was probably present in the ancient common ancestor of the PSEN1 and PSEN2 genes. Human PS2V and zebrafish PS1IV have highly divergent structures but conserved abilities to stimulate ?-secretase activity and to suppress the unfolded protein response (UPR) under hypoxia. The putative protein truncation caused by K115Efx10 resembles PS2V in its ability to increase ?-secretase activity and suppress the UPR. This supports increased Aß levels as a common link between K115Efx10 early onset AD and sporadic, late onset AD. The ability of mutant variants of PS2V to stimulate ?-secretase activity partially correlates with their ability to suppress the UPR. The cytosolic, transmembrane and luminal domains of PS2V are all critical to its ?-secretase and UPR-suppression activities. Our data support a model in which chronic hypoxia in aged brains promotes excessive Notch signalling and accumulation of Aß that contribute to AD pathogenesis.